THE CASE FOR TAX INTEGRATION AND CURRENT-BASE TAXATION - Fishbien, Nir (Columbia Journal of Tax Law, 2020)
The U.S. tax system has many distortions, but two triumph them all. The first is debt-over-equity. Under the current corporate double taxation mechanism, C corporations are incentivized to borrow rather than issue equity, because interest is deductible, and dividends are not. The second is foreign-over-domestic investment. Under the current U.S. international tax regime, U.S. multinationals are subject to a reduced tax rate, and in certain occasions are also exempt from U.S. tax on their foreign earnings, while their domestic earnings are subject to full corporate tax rate. In this Article, I call for the adoption of a Dividends-Paid Deduction form of tax integration and for current-base taxation of foreign earnings. The already reduced corporate tax rate (21%), combined with tax integration, will provide a significant relief from the relatively high burden of corporate double taxation, allowing U.S. multinationals to better compete in the global economy. It will eliminate (or substantially reduce) the debt-over-equity bias and the inefficient penalty on business activities carried through C corporations. Current-base taxation will eliminate the current incentive to invest and shift income abroad, while providing a very important source of revenue. It will also obliterate the need to distinguish between domestic and foreign earnings and as such will facilitate the adoption of tax integration, because all distributions of earnings that were previously taxed will give rise to the benefits of tax integration. Finally, in order to avoid a potential revenue loss as a result of this new dividends-paid deduction, a non-refundable full-rate withholding tax, or a new compensatory tax, equal to the rate of the corporate tax, should be introduced and implemented.